The Role of Interactive Whiteboards for Enhancing Teaching and Learning in Higher Education - Qader, Mahdi Azeez (Indonesian Journal of Curriculum and Educational Technology Studies, 2021)
More recently technology has opened up variety fortune doors in the education sector. Therefore, technology has become one of the important parts in the teaching and learning process. One of the technology tools may have enhanced the process is IWBs. This paper focuses on the significance of the interactive whiteboard to enhance the learning process by supporting different learners. Hence, this research used qualitative approach by using observation and interview methods. The data was collected at two private universities. 105 learners were observed, 15 students interviewed and 7 teachers questioned. The results illustrated that IWBs have significant impact to support different learning styles and increases the level of engagement. Abstrak Sekarang teknologi telah membuka banyak pintu peluang perubahan di dunia Pendidikan. Oleh karena itu, teknologi menjadi bagian yang sangat penting dalam proses belajar-mengajar. Satu jenis teknologi agaknya terkait dengan hal ini adalah papan tulis interaktif. Artikel ini focus pada signifikansi papan tulis interaktif dalam meningkatkan kualitas proses pembelajaran sebagai cara memfasilitasi belajar siswa. Data penelitian diambil dari dua universitas swasta, observasi dilakukan terhadap 105 mahasiswa, sebanyak 15 mahasiswa dan 7 guru diwawancara. Hasil penelitian ini menunjukkan bawah papan tulis interaktif memiliki dampak signifikan dalam menunjang berbagai ragam gaya belajar mahasiswa dan juga meningkatkan level keterlibatan mahasiswa.